Ictal high-frequency oscillations and hyperexcitability in refractory epilepsy. Issue 11 (November 2015) - Leung, Howan; Zhu, Cannon X.L.; Chan, Danny T.M.; Poon, Wai S.; Shi, Lin; Mok, Vincent C.T.; Wong, Lawrence K.S.
Highlights High-frequency oscillations captured at the onset of seizure may help determine surgical outcome in patients with refractory epilepsy. Cortical areas demonstrating hyperexcitability may be associated with ictal high-frequency oscillations. By examining hyperexcitability and ictal high-frequency oscillations, the decision-making process for surgical resection to treat refractory epilepsy may be improved with values of sensitivity and specificity that are more optimal.